EFEKTIVITAS KEPATUHAN MINUM OBAT TERHADAP STATUS GIZI PADA PENDERITA TUBERKULOSIS PARU (TBC) DI UPT PUSKESMAS BATURETNO - Nugroho Priyo Handono (Jurnal Keperawatan GSH, 2020)
Background: Pulmonary tuberculosis is an infectious disease that attacks the lung parenchyma, caused by Mycobacterium tuberculosis. This disease can also spread to other parts of the body, such as the meninges, kidneys, bones, and lymph nodes (Irman Soemantri, 2009). The prevalence of TB is estimated at 169 cases per 100,000 population, the incidence of pulmonary TB is 122 cases per 100,000 population and the mortality rate is 13 cases per 100,000 population (WHO, 2013). The prevalence of pulmonary TB in Central Java is 321 per 100,000 population (Riskes report, 2018). The Tuberculosis Case Notification Rate (CNR) for all cases was 118 per 100,000 population. Meanwhile, Wonogiri Regency was ranked 25th with CNR Tuberculosis of 75.2 per100,000 population (Central Java Health Profile, 2016). Purpose of writing: To determine the relationship between adherence to taking anti-tuberculosis drugs (OAT) with the nutritional status of patients with pulmonary tuberculosis at UPT Puskesmas Baturetno. Methods: The study design was observational with a cross sectional approach to 33 pulmonary tuberculosis patients who were undergoing outpatient care at the UPT Puskesmas Baturetno. Subjects were selected by purposive sampling. Drug adherence data were obtained from questionnaires filled out through interviews with patients. Food intake data were obtained through the Semi Quantitative Food Frequency Questioner and analyzed by Nutrisurvey. Nutritional status was assessed based on the Weight for Age Z Score (WAZ) referring to the WHO Antro 2005 reference standard. Bivariate analysis used SPSS 20 with the Chi Square statistical test. Results: Most of the subjects (57.6%) complied with the medication regimen. At the beginning of diagnosis, 18.2% of children were malnourished and decreased by 9.1% after treatment. There was no correlation between medication adherence and nutritional status (r = 0.218; p = 0.223). The relationship between medication adherence and nutritional status after being controlled by energy and protein intake did not show a significant relationship (r = 0.184; p = 0.322). Conclusion: There is no correlation between medication adherence and nutritional status of patients with ulmonary tuberculosis at Baturetno Public Health Center. Latar belakang : Tuberkulosis paru merupakan penyakit infeksi yang menyerang parenkim paruparu, disebabkan oleh Mycobacterium tuberculosis.Penyakit ini dapat juga menyebar ke bagian tubuh lain seperti meningen,ginjal,tulang,dan nodus limfe (Irman Soemantri,2009). Prevalensi TB diperkirakan sebesar 169 kasus per 100.000 penduduk, insidensi TB Paru sebesar 122 kasus per 100.000 penduduk dan angka kematian sebesar 13 kasus per 100.000 penduduk.(WHO,2013).Prevelensi TB paru di Jawa Tengah sebesar 321 per 100.000 penduduk (laporan Riskes,2018). Angka Notifikasi Kasus (Case Notification Rate = CNR) Tuberkulosis untuk semua kasus sebanyak 118 per 100.000 penduduk. Sedangkan Kabupaten Wonogiri menduduki peringkat ke-25 dengan CNR Tuberkulosis sebanyak 75,2 per 100.000 penduduk.(profil kesehatan jawa tengah,2016). Tujuan Penulisan: Untuk mengetahui hubungan antara kepatuhan minum Obat Anti TBC (OAT) dengan status gizi pasien TBC Paru di UPT Puskesmas Baturetno. Metode : Desain penelitian bersifat observasional dengan pendekatan Cross Sectional pada 33 penderita tuberkulosis paru yang menjalani rawat jalan di UPT Puskesmas Baturetno. Subyek dipilih secara purposive sampling. Data kepatuhan minum obat diperolah dari kuesioner yang diisi melalui wawancara dengan pasien. Data asupan makan diperoleh melalui Semi Quantitative Food Frequency Questioner dan dianalisis dengan Nutrisurvey. Status gizi dinilai berdasarkan Weight for Age Z Score (WAZ) mengacu pada baku rujukan WHO Antro 2005. Analisis bivariat menggunakan SPSS 20 dengan uji statistik Chi Square. Hasil: Sebagian besar subyek (57,6%) patuh terhadap aturan minum obat. Pada awal diagnosis sebanyak 18,2% anak mengalami gizi buruk kemudian mengalami penurunan sebesar 9,1% setelah pengobatan. Tidak terdapat hubungan kepatuhan minum obat dengan status gizi (r=0,218; p=0,223). Hubungan kepatuhan minum obat dengan status gizi setelah dikontrol oleh asupan energi dan protein pun tidak menunjukan hubungan yang bermakna (r=0,184; p=0,322). Kesimpulan: Tidak terdapat hubungan kepatuhan minum obat dengan status gizi penderita tuberkulosis paru di UPT Puskesmas Baturetno.